Stabilization Policy and the Costs of Dollarization - Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 2000)
This paper compares the welfare costs of business cycles in a dollarized economy to those arising in economies with different monetary arrangements. The alternative monetary policy regimes studied belong to three broad families: devaluation rate rules, inflation targeting, and money growth rate rules. The analysis is conducted within an optimizing model of a small open economy with sticky prices. The model is calibrated to the Mexican economy and is driven by three external shocks: terms of trade, world interest rate, and import-price inflation. We show econometrically that these shocks explain at a minimum 45 percent of the observed forecasting error variance of Mexican output and the Mexican real exchange rate at 8- to 16-quarter horizons. The model fits the data relatively well in the sense that it can account for the volatility and comovements of key macroeconomic indicators such as output, consumption, inflation, and the real exchange rate. The welfare comparisons suggest that dollarization is the least successful of the monetary policy rules considered: agents are willing to give up between 0.1 and 0.3 percent of their nonstochastic steady-state consumption to see a policy other than dollarization implemented.
Keywords: E58; F41; 330; Dollarization; Sticky Prices; Welfare Costs of Business Cycles